(untitled) (Journal of Bio-Science, 2021)
Pouzolzia sanguinea grows in tropical and sub-tropical regions of Bangladesh, used for a variety of purposes including pain, rheumatoid kidney diseases in traditional medicine. The crude ethanolic leaf extract of P. sanguinea with its different fractions (ethanol, n-hexane, and chloroform) was investigated for phytochemical constituents, in vitro antioxidant, anti-inflammatory effects, in-vivo analgesic and antipyretic activities. Preliminary phytochemical constituents were identified by chemical group test. P. sanguinea fractionated extracts contain alkaloids, glycosides, tannins, flavonoids, saponins, gums, and amides. Antioxidant activity test was performed by both qualitative (TLC and Rf value) and quantitative tests (inhibition of DPPH free radical scavenging). Extracts exhibited significant (p <0.001, p <0.0001) inhibition of DPPH free radical scavenging activity as compared to the standard drug ascorbic acid at similar doses. In vitro anti-inflammatory activity was determined by protein denaturation of egg albumin method. The percent inhibition of protein denaturation in the experiment of ethanol extract was found significantly higher (p <0.0001) compared with chloroform and n-hexane extracts. In addition, in vivo analgesic and antipyretic effects were determined in mice by acetic acid-induced writhing and yeast-induced pyrexia methods. The ethanol extracts of P. sanguinea exhibited inhibition of writhing reflex on mice by 71.58% at the dose of 500 mg/kg body weight which had greater analgesic activity than other n-hexane and chloroform extracts. In the anti-pyretic test, fractional extracts ethanol, chloroform, and n-hexane at a dose of 500 mg/kg body weight significantly (p <0.05) decreased pyrexia in mice up to 3 h as compared with the positive control paracetamol drug at a dose of 150 mg/kg body weight. In our in vitro and in vivo study models, it is evident that Pouzolzia sanguinea fractionated extracts showed significant antioxidant, anti-inflammatory, analgesic, and antipyretic activities. J. Bio-Sci. 29(2): 31-42, 2021 (December)